Arus Sosial dan Budaya Jepang pada Zaman Globalisasi - Amaliatun Saleha (Jurnal Kajian Wilayah, 2013)
Globalization is the term used to describe the economic expansion in the world at the end of the 20th century. Thus, the economic expansion followed by flows of culture, capital, people, images and ideologies. The five dimensions of global cultural flows can be termed ethnoscapes, technoscapes, financescapes, mediascapes, and ideoscapes. The impact of globalization on the labor market is the rise of the service industry, and the cultural effects of globalization is the shrinking of space and time by information technology, which can help the process of disseminating information to different parts of the world. In the 1990s, Japan achieved rapid development of dissemination of information via the internet, and had some important facts such as the upheaval of political party, the great earthquake in Kobe and the incident by Aum Shinrikyo. Since that time, there was a crisis of trust on the government and police, and some new sub-cultural movements as an anti-authoritarian, anti-bureaucratic and anti-industrial stance, and a concern for self-fulfillment, such as furitaa, enjo kousai, and otaku. Then, the rise of service industry worker and the increased of interest in Japanese pop culture (mass culture) in the world, stimulated commodification of culture and consumer culture. The flow of the Japanese pop culture shows that globalization does not always flow in one direction from the West to the rest, but can also flow from East to the various parts of the world, create fragmentation, cultural diversity and hybridity, and it is supported by the media.Keywords: globalization, global cultural flows, sub-cultural movements, commodification of culture, Japan since the 1990s